BEROAHAN, LOCAL TRADITION OF COMMMUNITY IN KOTABARU, MELAWI, WEST KALIMANTAN - M. Farid Migustio (The Pontianak State Institute of Islamic Studies, 2018)
Communities always have local wisdom for their interests and survival. Likewise with the community in Kotabaru, Tanah Pinoh District, Melawi Regency, West Kalimantan. Based on data obtained through interviews and observations at Kotabaru, the community inherited many local traditions; one of them is prayer. Beroah is a tradition of Kotabaru people who are of choice, carried out by people who want or want to do it, and usually carried out by capable communities. In the past until now prayers have always been carried out by Muslim communities to pray or send prayers to people who have died. The aim is to pray for people who have died. Prayers are usually carried out when the day of one's death and can also be carried out after the second, third, seventh, one hundred and even one day.